2016
DOI: 10.3389/fmicb.2016.01774
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Approaches to Screen Bioactive Compounds from Endophytic Fungi

Abstract: Endophytic fungi are capable of producing plant associated metabolites and their analogs with therapeutic value. In order to identify the potential endophytic isolates producing bioactive compounds, one need to screen all isolated endophytes, which may run into hundreds. Isolation of endophytic fungi is relatively a simple process; but screening of the isolated fungi for required metabolite production is a cumbersome process. Endophytic fungi producing plant associated metabolites may contain genes involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 83 publications
0
33
1
1
Order By: Relevance
“…Therefore, to protect these valuable medicinal plants and maintain the supply of PTOX for anticancer drugs, alternative sources are eagerly sought. Among these, endophytic fungi have the potential to produce PTOX 21 for the production of podophyllotoxin 21 . However, to date, only a few PTOX-producing fungi associated with Berberidaceae plants have been reported 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to protect these valuable medicinal plants and maintain the supply of PTOX for anticancer drugs, alternative sources are eagerly sought. Among these, endophytic fungi have the potential to produce PTOX 21 for the production of podophyllotoxin 21 . However, to date, only a few PTOX-producing fungi associated with Berberidaceae plants have been reported 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Even though these microorganisms still hold enormous biosynthetic potential, as demonstrated by recent genome sequence studies, a vast amount of novel fungal and/or bacterial taxonomic groups still lies unexplored [ 79 ]. To a large extent, this is due to limitations in traditional isolation procedures, as well as the non-culturable feature of many of these latter microorganisms [ 87 ]. To overcome this problem, molecular approaches, such as high-throughput sequencing and metagenomics, have become promising tools for unraveling the biosynthetic potential of hitherto uncultured microorganisms, evading the need for isolation of individual species [ 87 , 88 ], and thus providing an inexhaustible source of new microbial taxa.…”
Section: Discussionmentioning
confidence: 99%
“…To a large extent, this is due to limitations in traditional isolation procedures, as well as the non-culturable feature of many of these latter microorganisms [ 87 ]. To overcome this problem, molecular approaches, such as high-throughput sequencing and metagenomics, have become promising tools for unraveling the biosynthetic potential of hitherto uncultured microorganisms, evading the need for isolation of individual species [ 87 , 88 ], and thus providing an inexhaustible source of new microbial taxa. Genome mining and bioinformatics approaches also serve as powerful strategies towards the prediction of key biosynthetic clusters from genome sequence analysis data, providing a wealth of information that can be linked to cryptic secondary metabolites, as exemplified in the case of neothioviridamide ( 144 ) from Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that the production of bioactive metabolites depends greatly on the culture medium on which the fungus is grown [ 8 , 43 , 44 ]. In the present study, the best antimicrobial activity was observed when rice was used as a substrate.…”
Section: Mic and Mbc Of The Most Active Endophytic Strainsmentioning
confidence: 99%